The application of hybrid artificial intelligence techniques in the optimisation of crude palm oil production - ., Lily Amelia; Wahab, Dzuraidah; Hassan, Azmi (IEEE, 2008)
The production of crude palm oil and palm kernel are greatly influenced by factors such as deterioration of the raw material, processing inefficiency as well as environmental condition. An optimisation model for the palm oil production is therefore critical in ensuring maximum revenue in production whilst minimising palm oil and palm kernel losses and production cost. The proposed optimisation model is an integration between fuzzy expert system and multi objective programming model. Four fuzzy expert models were developed for each processing station with the aim of achieving four objectives, ie. to maximise revenue, minimise total production costs as well as minimise the total amount of palm oil and palm kernel losses. Two heuristic optimisation methods, ie. Genetic Algorithm (GA) and Direct Random Search are applied to solve this problem. The model is able to optimise the revenue, production cost as well as the total amount of palm oil and palm kernel losses. The study has also shown that Genetic Algorithm results in more optimum solutions compared to the Direct Random Search method